A Comparative In-vitro Dissolution Profiles of Generic and Branded Amoxicillin - Septilina Melati Sirait; Hanafi Hanafi; Lintannisa Rahmatia (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2020)
There are two types of Amoxicillin in the form of tablets, generic and branded medicines. Generally, drug products undergo systemic absorption through a series of processes, including disintegration of drug products followed by drug release, dissolution of drugs in aqueous media, and absorption through cell membranes into the systemic circulation. Dissolution profiles of generic and branded Amoxicillin were used to reference the public to choose generic Amoxicillin or branded Amoxicillin. It was because branded Amoxicillin is more expensive than generic Amoxicillin. This study aims to determine the dissolution profile and physical properties of both generic and branded amoxicillin tablets produced by the same pharmaceutical manufacturer. The Measurement of physical properties was carried out with several parameters: uniformity in weight and size, fragility test (friability), and disintegration test. All the results can meet the acceptance requirements that refer Indonesian Pharmacopoeia 5th edition in 2013. The physical properties result obtained by each. The dissolution test was done using an ultraviolet spectrophotometric method; dissolution tools were typed two apparatuses at 75 rpm with aquadest for 30 minutes, 37 ± 0,5 oC. The dissolution profile of generic Amoxicillin was declared identical or similar to branded Amoxicillin. It can be seen from F1 value = 3.40 and F2 value = 67.77, each of which meets the identical category's standard. Dissolution profiles of generic and branded Amoxicillin were declared identical, which means the Amoxicillin's quality control was equally excellent.